PENGARUH TRANSFORMASI DIGITAL DAN GAYA HIDUP TERHADAP PERILAKU KONSUMTIF (Studi Kasus Pengunjung Cafe MKA Binjai) - Risdayati, Wilma; Waqqosh, Abi; Sari, Darmaida (ITB AAS Indonesia Surakarta, 2024)
This research aims to find out how much influence digital transformation and lifestyle have on consumer behavior (case study of visitors to the Mka Binjai cafe). The method used in this research is a qualitative method with a descriptive approach. This data collection technique uses observation, interview and documentation techniques. This research shows that first, the influence of digital transformation has a big influence on customer satisfaction with the cafe. The new phenomenon of a cashless lifestyle supports consumer behavior. The cashless society lifestyle that is often carried out by the millennial generation makes them without hesitation be impulsive and consciously engage in consumer behavior.